Strategi Pemasaran Perbankan Syariah Berbasis Teknologi Informasi Pada Era Digital - Windi Febriani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Indonesia is a country with the potential to become the center of the world's halal industry, this is supported by the fact that the majority of the Indonesian population is Muslim, namely 86.7% of the total, occupying the first position with the largest Muslim population in the world. This fact should be a great opportunity for Islamic banking institutions to develop rapidly with well-organized and appropriate marketing strategies, so that it will have an impact on economic development in Indonesia. In this era that is completely focused on digital technology, sharia banking needs to take advantage of this to build its marketing strategy to expand its target market. This research was developed to determine technology-based sharia banking marketing strategies in the digital era. The method used in collecting information is a qualitative method and library presentation